Slovenia: Social Law and Labor Law – an Overview of Key Concepts - Mišić, Luka; Strban, Grega (Fundamentals of Labor Law in Central Europe, 2022)
The chapter, grounded in most relevant domestic literature on employment and labor relationships, provides the reader with a general overview of Slovenian individual and collective labor law regulation, its relation to EU law, and its placement in the wider field of social law, alongside social security law or social insurance regulation. It consists of an analysis of key sources of labor law, i.e., the Slovenian Constitution, the Employment Relationships Act or, simply, the Slovenian labor code,1 and autonomous legal sources like different-level collective agreements. Other important acts, like the Labor Inspection Act, Public Employees Act, or the Public Sector Salary System Act, are also referred to in places as to depict the regulatory framework as a whole. The chapter also addresses key aspects of most important labor law institutions, like the employment relationship, established by the employment contract, never staying far away from the evergreen interplay between labor law and (contract) civil law. It also considers some of the common challenges, faced in the field today, like disguised employment relationships or the conclusion of successive fixed-term contracts. Keywords: individual labor law, collective labor law, social law, constitution, Employment Relationships Act, employment relationship, employment contract, Slovenia